THE INFLUENCE OF CLASSROOM EXPERIENCE ON TEACHER BELIEF SYSTEMS: NEW FRENCH SECOND LANGUAGE TEACHERS’ BELIEFS ABOUT PROGRAM OPTIONS FOR ENGLISH LANGUAGE LEARNERS AND STUDENTS WITH LEARNING DIFFICULTIES - Arnett, Katy; Mady, Callie (McGill Journal of Education / Revue des sciences de l'éducation de McGill, 2018)
This longitudinal case study examines four new FSL teachers’ beliefs regarding the best and worst FSL program for English language learners and students with learning difficulties; the data are drawn from qualitative semi-structured interviews that occurred at the end of the participants’ Bachelor of Education program and near the end of each school year of their first three years of teaching. The case study considers how the teachers did or did not change their views as they gained experience in the classroom.